A heuristic approach towards variability of HC-128. (3rd April 2019) - Kumar, Arvind; Pal, S. K.; Ojjela, Odelu
Abstract: In this paper we consider the problem of variability of eSTREAM cipher HC-128. By variability of a cipher, we mean the maximum number of distinct key sequences that can be generated by the cipher. We present a heuristic analysis for variability of HC-128. Our analysis indicates that the cipher possesses maximum possible variability.